The Influence of Government Policy in Period Covid-19 Pandemic Against Stock Value Automotive Companies on the Indonesia Stock Exchange - Martias, Dony; Syafei, Jasmina; Adriyani, Annesa; Aswad, Hijratul (Indonesian Journal of Economics, Social, and Humanities, 2023)
The purpose of this research find out the difference in stock returns from before and after the announcement of the first national case of covid-19 and the announcement of the PPKM Emergency Covid-19 and to find out the difference in stock transaction volume from before and after the announcement of the first national case of covid-19 and the announcement of the PPKM Emergency Covid-19.The population in this study were 15 automotive and component sub-sector companies on the Indonesia Stock Exchange (IDX), using a purposive sampling technique so thatobtained a sample of 8 companies. The observation period used in this study is a period of 31 days around the event date, namely 15 days before the event, 1 day during the event, and 15 days after the event. Data analysis using test parametric paired sample t-test, but if the data is not normally distributed, a non-parametric statistical test is used, namely the Wilcoxon signed rank test. The results of this study indicate that there are differences in stock returns from before and after the national announcement of the first case of Covid-19, there are no differences in stock returns from before and after the announcement of the Covid-19 Emergency PPKM, there are differences in the volume of stock transactions from before and after the national announcement of the first case Covid-19, there are differences in the volume of stock transactions before and after the announcement of the Covid-19 Emergency PPKM.